Pendekatan Biologis dalam Pemulihan Tanah Terdegradasi pada Agroekosistem Tropis: Systematic Literature Review Tentang Interaksi Biochar, Mikroorganisme, dan Dinamika Bahan Organik Tanah - Gian Sapta Adrialin; Ratna Suminar (Universitas Tidar, 2026)
Soil degradation in tropical agroecosystems is a critical issue that directly impacts agricultural productivity, ecosystem stability, and environmental sustainability. In recent years, interest in biological soil restoration approaches has grown significantly, as they are considered more effective in supporting sustainable soil management compared to conventional approaches reliant on chemical inputs. This study aims to examine the development of research on the restoration of degraded soils in tropical agricultural systems, identify dominant trends in findings, and identify research gaps in the available scientific literature. The review was conducted using a Systematic Literature Review (SLR) approach, adhering to the PRISMA guidelines as the basis for the literature selection and analysis process. Article searches were conducted through the Scopus, Web of Science, Dimensions, and Google Scholar databases, covering publications from 2017 to 2024. The selection process was conducted systematically, based on inclusion and exclusion criteria, resulting in 42 scientific articles suitable for further analysis. The synthesis results indicate that research on tropical soil restoration largely focuses on the use of biochar, soil microorganisms, carbon dynamics, and an integrative approach that combines biochar, microbes, and plants. In addition, recent research developments indicate a paradigm shift toward a more adaptive, holistic, and multidisciplinary approach to biological restoration. This study is expected to enhance the conceptual understanding of biologically based tropical soil restoration, serving as a foundation for the development of further research on more sustainable agroecosystem restoration strategies.